Characterization of MnWO4with flower-like clusters produced using spray pyrolysis - Somchai Thongtem (2018)
MnWO4(huebnerite) with flower-like clusters of nano-plates was produced from the solutions containing MnCl2·4H2O and Na2WO4·2H2O by the 300 °C spray pyrolysis. The phase was detected by X-ray diffraction (XRD) and selected area electron diffraction (SAED), and is in accordance with the results characterized using energy dispersive X-ray (EDX) analysis. The flower-like clusters of nano-plates were characterized using scanning and transmission electron microscopes (SEM and TEM), and their parallel lattice planes using a high resolution transmission electron microscope (HRTEM). Vibration spectra of the huebnerite structured products were characterized using Raman and Fourier transform infrared (FTIR) spectrometers. Their photoluminescence (PL) emissions are in the same spectral region at 405-412 nm. © 2009 The Nonferrous Metals Society of China.